Evaluating the business model innovation of small snack food production enterprises in China based on the varim model - Li Haibo; Noor Fzlinda Fabeil (Penerbit Universiti Malaysia Sabah, 2023)
This paper examines the business model innovation situation, evaluation, and key factors of small snack food production enterprises in China and provides suggestions for enterprises. A questionnaire designed using the VARIM model evaluates business model innovation based on five aspects, combined with the influential role of relational resources, digital technology, and long tail theory. It is hypothesized that relational resources, digital technology, and long tail theory have a positive impact on business model innovation, and that the VARIM model assesses profitability potential. It is hypothesized that firms should utilize these factors for business model innovation to improve competitiveness and sustainability. The findings and conclusions of this paper are based on assumptions and speculations, which need to be verified and corrected by subsequent practical investigations.